Wort und Wandlung : Senecas Lebenskunst - Albrecht, Michael von. (Mnemosyne, Supplements, 2004)
The most important medium of Seneca's Lebenskunst is language. We first change the meaning of words through philosophical reflection; then we can change ourselves through language. Each chapter in this book takes linguistic or stylistic observations in texts as starting point (e.g. metaphors from the domains of health, finance, and sea-faring). Topics are man's self-definition in time and place and his relation to property, learning, and tradition. Single words and rhetorical patterns guide us in constructing an inner world and to find our own identity. Texts in Latin and in translation document Seneca's importance for modern, Christian Europe.